THE INTEGRATION OF ISLAMIC PERSPECTIVES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE: A SYSTEMATIC LITERATURE REVIEW - Sidqurrahman, Zia (Journal of Social and Economics Research, 2024)
The integration of Islamic perspectives in teaching English as a Foreign Language (EFL) represents a growing area of interest in education, aiming to align pedagogical practices with faith-based values. This study systematically reviews the literature to explore how Islamic principles have been incorporated into EFL teaching methodologies and curricula. A systematic approach was employed, analyzing peer-reviewed articles from reputable databases, focusing on conceptual frameworks, practical applications, and pedagogical challenges. The findings reveal a significant emphasis on moral education, cultural sensitivity, and the alignment of language instruction with Islamic values. Islamic-based EFL approaches enhance student engagement by fostering ethical awareness and respect for diverse cultures while simultaneously achieving language proficiency goals. However, challenges such as balancing religious content with secular learning objectives and adapting materials for global contexts persist. This study highlights the need for further research into innovative strategies that address these challenges and ensure effective implementation. The findings contribute to the body of knowledge in educational practices by offering a framework for integrating Islamic perspectives into EFL teaching, benefiting educators, policymakers, and curriculum designers. Future research directions and policy implications are discussed, underscoring the importance of culturally responsive pedagogy in a globalized educational landscape.